A mathematical model for through-air drying process of yarn bobbins. Issue 5 (4th May 2022) - Akyol, Ugur; Karakoca, Alper; Shaliyev, Rafayel; Kahveci, Kamil; Cihan, Ahmet
Abstract: In this study, a mathematical model has been developed to simulate the through-air drying process of yarn bobbins. For this purpose, experimental data was obtained in a prototype experimental set up by passing pressurized hot air through the wool yarn bobbins. First of all, the physical phenomenon expressing the drying process has been reduced to the heat transfer problem and then a mathematical model has been written for the drying process which also includes the convective term. Using the experimental data, the coefficient included in the mathematical model was found by the extremal method. So, an inverse problem was solved. The accuracy of the model was checked by comparing with the experimentally obtained temperature values after solving a direct heat transfer problem in the given conditions. Good correlation between the obtained model results and the experimental results shows the accuracy of the mathematical model.